2017
DOI: 10.1186/s12947-017-0105-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of multi-organ ultrasound with pocket-sized device in the management of acute dyspnea

Abstract: BackgroundThe availability of ultra-miniaturized pocket ultrasound devices (PUD) adds diagnostic power to the clinical examination. Information on accuracy of ultrasound with handheld units in immediate differential diagnosis in emergency department (ED) is poor. The aim of this study is to test the usefulness and accuracy of lung ultrasound (LUS) alone or combined with ultrasound of the heart and inferior vena cava (IVC) using a PUD for the differential diagnosis of acute dyspnea (AD).MethodsWe included 68 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 30 publications
2
62
0
1
Order By: Relevance
“…However, similar to or even extending limitation of less conservative approaches, pocket ultrasound device assessment limited to lung ultrasonography and eyeball classification of EF cannot rule out the possibility of decompensated HF with preserved EF (HFpEF). Thus, to try to improve PUD diagnostic accuracy, another parameter possibly extending this evaluation to the context of HFpEF was needed …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, similar to or even extending limitation of less conservative approaches, pocket ultrasound device assessment limited to lung ultrasonography and eyeball classification of EF cannot rule out the possibility of decompensated HF with preserved EF (HFpEF). Thus, to try to improve PUD diagnostic accuracy, another parameter possibly extending this evaluation to the context of HFpEF was needed …”
Section: Discussionmentioning
confidence: 99%
“…The concordance between cardiac ultrasonography by pocket ultrasound device (PUD) and standard echocardiography has been recently assessed, and the use of PUD confirmed to be feasible and reliable even by medical resident . Recently, we demonstrated that in a population of patients presenting to the ED for the recent onset of acute dyspnea, the integrated ultrasound examination of lung‐heart‐inferior vena cava with a PUD is feasible and has reliable diagnostic value for the diagnosis of dyspnea of cardiac origin, but the main limitation of this study was the difficulty to identify patients with HF with preserved EF (HFpEF). Evaluation of BNP levels in patients with acute HFpEF can be misleading, especially in patients with concomitant obesity who can have BNP levels below the clinically accepted thresholds …”
Section: Introductionmentioning
confidence: 98%
“…Lung and cardiac ultrasound examination during acute dyspnea allow to gather important diagnostic information useful to establish correct therapeutic approach, particularly in complex clinical cases. The integrated ultrasound examination (IUE) of lung–heart–IVC with pocket ultrasound devices is an extension of the clinical examination, increasing efficiency, and speed in the differential diagnosis of acute dyspnea in ED …”
Section: Assessment Of Patients With Acute Dyspneamentioning
confidence: 99%
“…In patients hospitalized for heart failure, quantification of extravascular lung water is feasible and comparable with that obtained with high‐end ultrasound system . We have recently proposed a validated protocol for the evaluation of dyspneic patients using a PUD that allows to correctly identify patients with dyspnea of cardiac and noncardiac origin (Movie ). Thorax should be examined in two scans at each side (4 zones): anteriorly on the II intercostal space, mid‐clavicular line and laterally on the V intercostal space, mid‐axillary line, to sample upper and lower lungs.…”
Section: Assessment Of Patients With Acute Dyspneamentioning
confidence: 99%
“…Chest X-ray showed massive right pleural effusion and atelectasis of lower and median lobes ( Figure 1). Multi-organ ultrasound [1] showed normal cardiac structure and function, massive pleural effusion in the right side ( Figure 2) and A-profile in the left lung. The patient received oxygen therapy with Venturi mask (FiO 2 50%) with improvement of saturation and mild reduction of tachypnea (SaO 2 94%, respiratory rate (RR) 30 breaths/min).…”
Section: Case Reportmentioning
confidence: 99%